Potensi Ekstrak Air Kayu Manis (Cinnamomum burmanii) Sebagai Agen Neuroprotektif Pada Penyakit Parkinson Dengan Model Mencit Jantan (Mus musculus) Yang Diinduksi Haloperidol - Mentari, Ika Ayu; Azmi, Rizky Nur; Astriani, Nur Atika; Kamilah, Lila Zulfa (Media Farmasi, 2024)
Parkinson's disease (PP) is a neurodegenerative disease, Parkinson's occurs due to mitochondrial dysfunction caused by oxidative stress. Compounds that can prevent the formation of oxidative stress are antioxidants. One plant that has a role or activity as a high antioxidant is cinnamon (Cinnamomum burmani). This study aims to determine the antioxidant activity, total phenols and total flavonoids of cinnamon water extract and the effect of the dose concentration of cinnamon water extract on reducing the symptoms of Parkinson's disease in mice that have been induced by Haloperidol. Total phenols used the Follin-Ciocalteu method, total flavonoids used the colorimetric method with AlCl3 reagent. The antiparkinson test used 30 male mice divided into 5 test groups such as group I healthy, group II levodopa, group III Haloperidol, groups IV, V, and VI given cinnamon water extract at successive doses of 200; 400;800 mg/KgBW. Groups II-VI were given Haloperidol induction at 45 minutes after treatment. The tests were carried out on the pole test, rotarod test and sense of smell observations were carried out for 14 days with data collected every day 0, 4, 7, 11 and 14. The results showed that cinnamon water extract had a total phenol content of 617.2 mg GAE/g and total flavonoids 565 mg GAE/g, and has an antioxidant activity IC50 of 4.124 μg/mL. ANOVA analysis with Tukey's follow-up test in the rotaroad test showed significantly different in dose 200,400 and 800 mg/kgBW with the haloperidol group (P <0.05), as well as the ability of the sense of smell when compared with Haloperidol giving 800 mg/KgBW extract significantly different (P<0.05). Cinnamon extract can reduce the symptoms of parkinsonis in mice induced by haloperidol in effective dose 800 mg/kgBW and has strong antioxidant activity.